The effectiveness of Drug Rehabilitation Module on the motivation achievement among male inmates in Malaysia. - Ahmad, Jamaludin; Sulaiman, Tajularipin; Alias, Siti Rahmah (Canadian Center of Science and Education, 2010)

(untitled)
This study on the effects of a Drug Rehabilitation Module on the motivation achievement of Rehabilitation Centre inmates used an experimental research design. Sixty-six respondents of the centre participated and were randomly assigned to the experimental and control groups. Each group comprised of 33 subjects. The hypotheses were tested using t-test and Pearson correlation statistics. Result showed that there is a significant difference between the pre and post-test measures of motivation achievement in the experimental group, thus proving the effectiveness of the Drug Rehabilitation Module in increasing motivation achievement among Rehabilitation Centre inmates, t (32) = -3.88, p = 0.001. Results also show that there is a significant difference in motivation achievement between the experimental and control groups, t (32) = -3.82, p = 0.001 at ? = 0.05. However, result show that the mean score difference was more pronounced for the experimental group (M=111.21), compared to the control group (M=85.94). In summary, results show that the motivation achievement of rehabilitation centre inmates can be improved using the module mentioned above. Achievement motivation is a person’s desire to achieve a goal. Hence, more studies with better control need to be conducted to confirm the effectiveness of the above module. The study aimed to determine the effectiveness of the module on inmates in Rehabilitation Centre. The study also emphasized motivation achievement being measured from various aspects such as goal setting, perseverance, expectattion for success, anxiety level, risks, and attitude as important characteriscs of resilience. Hence, it is concluded that the rahabilitation module can be used to improve the motivation achievement of Rehabilitation Centre inmates.